Peran Manajemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan Pada PT. Freight Express Surabaya Cabang Makassar - Andi Irfa; Abdul Sadiqin Sadiq; Jumaidah Jumaidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the role of HR management at PT Freight Express Surabaya Makassar Branch. This research uses qualitative research by looking at the role of human resource management at PT Freight Express Surabaya Makassar Branch. And for data analysis used, namely reviewing the data, reducing the data, compiling the reduced data, presenting the data and checking the validity of the data and drawing conclusions. The results of the research show that the role of HR Management in improving employee performance is to direct and control all employees so that they are effective in carrying out work by evaluating employee performance and ensuring that each employee carries out the duties and responsibilities according to their job and the management carries out job training to improve skills and performance assessment in human resource procurement. The efforts that have had a positive impact on employees that have been carried out by management are fulfilling employee rights by providing compensation and job training to improve skills and increase career paths as well as providing performance targets for each employee.